Climate Change and Agricultural Exports in Sub-Saharan Africa: The Mediating Roles of Institutional Capacity - Sunday Osahon Igbinedion; Ngozi Alison Mokobia (CV. Proaksara Global Transeduka, 2025)
This study investigated the effect of climate change on agricultural exports in Sub-Saharan Africa (SSA) region taking into consideration the mediating effects of four (4) institutional capacity variables. The study covered 29 sampled SSA countries from 2013 to 2022. The study adopts the System Generalized Method of Moments (SGMM) estimation technique. The System Generalized Methods of Moments (SGMM) reveals that climate change positively influences agricultural exports. However, government effectiveness and accountability had a negative significant effect on agricultural exports. Interaction effects show that government effectiveness, political stability, regulatory frameworks, and accountability positively mediating the effect of climate change on agricultural exports but rule of law has a negative mediating effect. Robustness tests (Hansen J and serial correlation tests) both confirm that the model and instruments are reliable. The study submits that, the SSA region can optimize the benefits of climate change while addressing regulatory and legal constraints by leveraging on effective governance and institutional frameworks. Lastly, the SSA government builds robust, effective institutions to improve governance and accountability.